Hubungan Efikasi Diri dengan Kualitas Hidup Penderita Penyakit Paru Obstruktif Kronik (PPOK) di RSUD Dr. Moewardi - Roosana, Sarah Nadya; Harsini, .; Suradi, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Chronic Obstructive Pulmonary Disease COPD) is one of the causes of respiratory disorder that is often found in the world. Along with the increase in COPD complications, patients require a special effort to prevent lung decline of function in order to improve the quality of life. One of the ways is increasing self-efficacy. This study aims to determine the relationship between self-efficacy and quality of life in patients with COPD at RSUD Dr. Moewardi. Methods: This study was an observational analytic with cross-sectional approach. Samples of this study were 40 COPD patients in the outpatient pulmonary clinic of RSUD Dr. Moewardi were selected using purposive sampling technique. The independent variable of this study is self-efficacy which was measured with the COPD Self-Efficacy questionnaire (CSES). The dependent variable of this study is quality of life as measured by COPD Assesstment Test (CAT) questionnaire. The confounding variables of degree of smoking, duration of COPD, and the degree of breathlessness measured by respondent characteristics questionnaire and Modified Medical Research Council scale (mMRC scale). The data were analyzed using multiple logistic regression models. Results: Results of multiple logistic regression analysis showed the results OR = 72.055; CI 95% from 1300 to 3944.041; and p = 0.037. This result has controlled the confounding variables, namely the long-suffering COPD, degree of smoking and degree of breath shortness. Patients who have good self-efficacy have a good quality of life for seventy-two times greater than patients who have poor self-efficacy. Conclusions: There is significant correlation between self-efficacy and quality of life of patients with Chronic Obstructive Pulmonary Disease (COPD) at RSUD Dr. Moewardi. Keywords: COPD, Self-Efficacy, Quality of life. Â